Analysis Of Meat Demand In Malaysia Model Choice Between Rotterdam And Aids. - S.Paraguas, Maria Divina; Kamil, Anton Abdulbasah (2005)
Aggregated time series data for differentiated meat products namely, beef pork, poultry and mutton were used to estimate and analyze Malaysian market demand for meats.